ENERGETICAL PARAMETERS OF THE SOLAR STATION (Web of Technology: Multidimensional Research Journal, 2025)
The purpose of the work is the theoretical simulation to determine the insolation parameter for solar photovoltaic station. The coefficient of insolation describes the effectiveness of future work photovoltaic cells in certain seasons and periods of time. To calculate the power of a solar station, we take into account the level of insolation, because in each region it is different, and accordingly the power of the panels will also be different And also the factor that allows to measure how much the sun shines in a particular region. Analysis of the distribution of the intensity of total solar radiation according to these data showed a high efficiency of using solar energy for a definite month.